(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2019)
Photoionization data of the trans-Fe element Rb\(^2+\) are reported. Rydberg series 4s\(^2\)4p\(^4\)(\(^1\)D\(_2\))nd and 4s\(^2\)4p\(^4\)(\(^3\)P\(_1\))nd Rydberg series of Rb\(^2+\) from the \(^2\)P\(^°\)\(_3\)\(_/\)\(_2\) ground state and the \(^2\)P\(^°\)\(_1/2\) metastable state of Rb\(^2+\) converging respectively to the 4s\(^2\)4p\(^4\)(\(^1\)D\(_2\)) 4s\(^2\)4p\(^4\)(\(^3\)P\(_1\)) series limit in Rb\(^3\)\(^+\) are considered. Calculations are performed in the framework of the Screening constant by unit nuclear charge (SCUNC) method. Accurate data are tabulated up to n=40. It is shown that the SCUNC analytical formulas reproduce with an excellent precision, recent ALS measurements of Macaluso et al. [J. Phys. B: At. Mol. Opt. Phys. 49 (2016), 235002; 50 (2017), 119501)]. The energy deviations with respect to the ALS data are equal to 0.001 eV. New data are tabulated for \(n=21-40\).